AI, Blockchain, ERP, and Machine Learning in Fisheries Supply Chain Optimization: A Systematic Literature Review - Irfan Dadi; Iveline Anne Marie; Dadang Surjasa; Juniati Gunawan (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2026)
Getting a fully digital infrastructure set up for fisheries has become difficult, yet so has understanding how to develop the infrastructure to improve both sustainability and operability. Fish products are especially troubling because they are so perishable. Coordinating the large number of small fishing businesses (which are the main focus of this paper) is troublesome and causes a lack of ability to trace products throughout the supply chain, and a whole host of other inefficiencies. In an attempt to better understand the challenges of technology integration in small-scale fisheries, this paper presents several case studies of how artificial intelligence, machine learning, blockchain, and enterprise resource planning tools have been implemented in fisheries supply chains. In line with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) methodology, the review captures the state of technology in the field by reviewing 111 articles published in the last five years via a systematic search of Scopus and the Web of Science. The bibliometric tool in R was used to process the bibliographic data and ensure a systematic review of the published works. From this analysis, it was found that AI and machine learning tools were primarily used for demand and supply forecasting, whereas blockchain was used to ensure traceability and transparency in the supply chain. ERP tools were used to integrate the logistics, financial, and inventory management systems. While these tools have been implemented, there still appear to be significant barriers to integrating these technologies in a digital ecosystem. The barriers to implementation include high costs, very little digital infrastructure, and a complete unwillingness to adopt the technologies. The review indicates that the use of technology needs to be integrated, and the best way to improve small-scale fisheries is through the use of technology that is flexible, scalable, and can be easily integrated. These solutions lay the groundwork for better sustainable fisheries management. Further down the line, research can focus on creating interconnected systems that make it possible to implement affordable traceability and data-sharing systems, as well as provide real-time decision support across the various stages of the fisheries value chain.